2013
DOI: 10.1242/jeb.085746
|View full text |Cite
|
Sign up to set email alerts
|

A thermogenic secondary sexual character in male sea lamprey

Abstract: SUMMARYSecondary sexual characters in animals are exaggerated ornaments or weapons for intrasexual competition. Unexpectedly, we found that a male secondary sexual character in sea lamprey (Petromyzon marinus) is a thermogenic adipose tissue that instantly increases its heat production during sexual encounters. This secondary sexual character, developed in front of the anterior dorsal fin of mature males, is a swollen dorsal ridge known as the 'rope' tissue. It contains nerve bundles, multivacuolar adipocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The amount of these fatty acids comprised of SFAs, MUFAs and PUSAs were 41.8%, 40.7%, and 17.4%, respectively, in the TFA mixture. Previous research on extracts of whole sea lamprey or tissues (muscles, liver and intestines) showed little or no C12:0 fatty acid present in the FFA profiles [1820,32]. Our findings showed a high content of C12:0 fatty acid (9%) in the TFA mixture from the adult migratory sea lamprey skin ( Table 2 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The amount of these fatty acids comprised of SFAs, MUFAs and PUSAs were 41.8%, 40.7%, and 17.4%, respectively, in the TFA mixture. Previous research on extracts of whole sea lamprey or tissues (muscles, liver and intestines) showed little or no C12:0 fatty acid present in the FFA profiles [1820,32]. Our findings showed a high content of C12:0 fatty acid (9%) in the TFA mixture from the adult migratory sea lamprey skin ( Table 2 ).…”
Section: Discussionsupporting
confidence: 53%
“…There are also several reports on total fatty acid profiles from muscles from sub-adult sea lampreys during migration from river basins in Portugal [12,18,19], and a fatty acid profile of the rope tissues from sexually-mature sea lampreys from Lake Huron, Michigan, thought to play a role in mating [20]. We are working to characterize numerous compounds present in migratory sea lamprey skin, including an alarm cue thought to be important in the detection and avoidance of predation during migration [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sexually mature female G. australis possessed a raised ridge of tissue in front of the anterior dorsal fin, which resembled the 'rope' seen in mature male sea lamprey. At the final stage of sexual maturation, adult male sea lamprey develop a rope-like thickening on their dorsal ridge that extends from the posterior gill slit to the beginning of the anterior dorsal fin (Chung-Davidson et al 2013). Presently believed unique to male sea lamprey, the rope is a thermogenic secondary sexual characteristic that produces heat in the presence of an ovulated female, but not in the presence of other males (Chung-Davidson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Across both monitoring years, a morphological characteristic evident in all six sexually mature females but absent in male lamprey, was the presence of a raised dorsal ridge in front of the anterior dorsal fin (Fig. 4), visually similar to the 'rope' of the male sea lamprey (Hardisty and Potter 1971;Chung-Davidson et al 2013).…”
Section: Behaviour and Morphology Of Post-spawning Fishmentioning
confidence: 95%
“…Plasma samples were also used to measure circulating concentrations of the male lamprey pheromone using ELISA . Measurements of the dorsal rope (Chung-Davidson et al, 2013a) were taken weekly using calipers, and differences between treatment groups were tested using a two-way ANOVA, with time and treatment as the independent variables, followed by Fisher's LSD. Expressed fluids were checked under a microscope to determine presence of sperm.…”
Section: In Vivo Functional Experimentsmentioning
confidence: 99%